2020
DOI: 10.3389/fimmu.2020.00989
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in the Context of Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Myeloid-derived suppressor cells (MDSCs) are innate immune cells that acquire the capacity to suppress adaptive immune responses. In the context of allogeneic hematopoietic stem cell transplantation (allo-HSCT), MDSCs (in the donor graft and in the recipient, after allo-HSCT) might mediate immune suppression through multiple mechanisms. However, it remains unclear how MDSCs can be distinguished from their normal myeloid counterparts in the hematopoietic stem cell donor graft and during immune reconstitution af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…A higher presence of Tregs was also reported in those patients (50). Other studies suggest alternative mechanisms such as a strengthened crosstalk between MDSCs and Tregs or NKT cells (28,51). In agreement with these studies, an increase of the myeloid cell compartment was also observed at day 28 post-HCT after treatment with UnLicNK cells, but an increase on CD4 T cells or NKT cells was not observed at this time point in the organs analyzed.…”
Section: Discussionsupporting
confidence: 81%
“…A higher presence of Tregs was also reported in those patients (50). Other studies suggest alternative mechanisms such as a strengthened crosstalk between MDSCs and Tregs or NKT cells (28,51). In agreement with these studies, an increase of the myeloid cell compartment was also observed at day 28 post-HCT after treatment with UnLicNK cells, but an increase on CD4 T cells or NKT cells was not observed at this time point in the organs analyzed.…”
Section: Discussionsupporting
confidence: 81%
“…The traditional classification of myeloid cells in the periphery and MDSC at the tumor site have recently been revised using several modern technologies, aiming at categorizing single cells based on their gene signature (single-cell RNAseq) and expression of cell surface receptors and some intracellular proteins (mass cytometry, CyTOF). The basic hypothesis is that, beyond the variety between human and mouse in the classification of these cells (24), in each species, the gene signature and cell surface protein expression may vary depending on the organ from which cells are isolated (BM, spleen, blood, LNs, tumor site) and may also differ between tumor types (122)(123)(124)(125)(126). These studies are still in early development but may pave a new direction in scientific research and its translational implications.…”
Section: A Future View Of the Classical Two-stage Model In Light Of Mmentioning
confidence: 99%
“…Generating MDSCs from human is difficult due to low concentration. More than one month of cultivation is required to produce sufficient MDSCs which might be too long for their application as a treatment for severe acute GVHD, whereas the ideal method for their processing has not yet been identified [ 91 ].…”
Section: Gvhd Pathophysiology and Implications For Mdscsmentioning
confidence: 99%